High performance quaternary logic designs using GNFETs - Shaik Javid Basha; P. Venkatramana (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2023)
The implementations of quaternary circuit schematics are presented in this paper. The quaternary logic is a better choice over the conventional logics because it offers high operating speed, reduced chip area and reduced on-chip interconnects. A new method is presented to design quaternary schematics using graphene nanoribbon field effect transistors (GNFETs). The dimer line of graphene nanoribbon (GN) is used to control the threshold voltage of GNFETs. Four quaternary logic inverter circuits such as standard quaternary inverter (SQI), intermediate quaternary inverter (IQI), positive quaternary inverter (PQI) and negative quaternary inverter (NQI) along with the NAND and NOR circuits are proposed. Furthermore, the quaternary half adder circuit is designed that helps to develop complex designs. The HSPICE simulator is utilized for simulating the proposed designs to obtain the performances such as delay, power and power delay product (PDP). The obtained circuit performances are compared with carbon nanotube FETs (CNFETs) based circuits. The comparison results show that the proposed GNFET circuits achieved 53.51% of overall performance improvement over the CNFET circuits.